HIV in Women: The Gynecological Frontier - Goswami, S; Chattopadhyay, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The objective of the paper was to study the spectrum of gynecological disorders in HIV positive woman, which are often not given much importance as the issue of antiretroviral therapy and management of opportunistic infections occupy the major share of their treatment strategy. Methods: It was an observational study which included 135 women. The study was conducted in the Medical College and Hospital, Kolkata from January 2010 to December 2012 after obtaining permission from the institutional ethics committee. All the HIV positive women who came to the gynecological outpatient department with gynecological complaints were included in the study. Results: The seropositive women suffered from the same range of gynecological problems as in non-infected women. The most common complaints at presentation were vaginal white discharge and pruritus vulvae. The most common post-operative complication was fever. Conclusions: The HIV/AIDS is taking the shape of a generalized epidemic and with the advances in the antiretroviral therapy, the life expectancy of the patients is increasing. With the improvement of survival more and more of HIV positive women would present with problems pertaining to any system of the body and the gynecological complaint is not an exception. Addressing these problems would lead to boosting up of the care and support of this subset of women. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 21-25 DOI: http://dx.doi.org/10.3126/njog.v8i2.9761